If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + 14 = 2a + 3 Reorder the terms: 14 + a = 2a + 3 Reorder the terms: 14 + a = 3 + 2a Solving 14 + a = 3 + 2a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2a' to each side of the equation. 14 + a + -2a = 3 + 2a + -2a Combine like terms: a + -2a = -1a 14 + -1a = 3 + 2a + -2a Combine like terms: 2a + -2a = 0 14 + -1a = 3 + 0 14 + -1a = 3 Add '-14' to each side of the equation. 14 + -14 + -1a = 3 + -14 Combine like terms: 14 + -14 = 0 0 + -1a = 3 + -14 -1a = 3 + -14 Combine like terms: 3 + -14 = -11 -1a = -11 Divide each side by '-1'. a = 11 Simplifying a = 11
| 5(5x+1)=20 | | [2(1+3)+1]*7+1= | | x^2+16x+8=8x-4 | | 108-5x=13x+22 | | x^2-8x+12=5 | | 11x^2-8x+8=0 | | (2a+6*2)x(3a+3)+a= | | 128-5x=3x+8 | | (2a+12)x(3a+3)+a= | | 143-3x=33x+15 | | 2x-x^3+5=0 | | 5p+p-4p= | | x*x+x=420 | | X^2-5X-23=0 | | 3-3p=4-2p | | 6x^2-2x=-x+6x^2 | | 14g= | | 107-6x=12x-21 | | 375.6m= | | x^5-x+3=0 | | 97-3x=7-8x | | 2x+1=+5 | | 2x^2-6x+2x-6=0 | | 1,5=0,15 | | -6u-5=13 | | x^2+27x-28=0 | | (x+1)(2x-6)=0 | | 23s+45=19s-39 | | 7t-17=6t+16 | | 12x-4=7x+14 | | 5x+9=2x+36 | | 4-6x=6x+10 |